If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8=-6u+2(u+2)
We move all terms to the left:
8-(-6u+2(u+2))=0
We calculate terms in parentheses: -(-6u+2(u+2)), so:We get rid of parentheses
-6u+2(u+2)
We multiply parentheses
-6u+2u+4
We add all the numbers together, and all the variables
-4u+4
Back to the equation:
-(-4u+4)
4u-4+8=0
We add all the numbers together, and all the variables
4u+4=0
We move all terms containing u to the left, all other terms to the right
4u=-4
u=-4/4
u=-1
| 35=-3(3x+15)-(10+x) | | 11-2m-6=2+2m | | 9(6x+12)=16-10(x+2) | | -1/2=-2/3x+2/7 | | +3x=+5 | | 2/3x=11/28 | | -5x+3+x=9+x | | 9(6x+12)=16-(x+2) | | 9^x=3^1-2x | | 20x-60=24-3x | | 7(7x+14)=11-(x+2) | | 8-x=37 | | (x+1)(3x-1)-(5x+1)=0 | | 3x-(2x-11)=15 | | 2w=157 | | (2m-1)^(2)=49 | | 8/y+4/y=3 | | -(t-19)=28 | | 8+7n=4n+8 | | (4x-2)=3x+6 | | 4x+3x-7=33-2x-13 | | 9b-5b+2=28-6-b | | 4x+7-8(x+1)=2x+4 | | 8s-7=4s(s+2) | | 8s-7=4s(s+20 | | 5+10m=1/2(8+20m) | | p-1/4×3=5/6 | | 13-4x+14=15 | | 14/1*1*9-(4-4*6)=x | | 4x+4x+4x+1=24-11x | | 14/1/1*9-(4-4*6)=x | | 7/9=x/50 |